The Rate of Return to Driving after Traumatic Brain Injury in Malaysia and the Changes in Driving Behaviour - Hasnol Basri, Nurul Firdausi; Mazlan, Mazlina (ASEAN Journal of Rehabilitation Medicine, 2021)
Objectives: To examine the rate of return to driving among patients with traumatic brain injury (TBI) in Malaysia and its associated factors; and to identify the changes in their driving behavioural pattern. Study design: A cross sectional study. Setting: A tertiary hospital in an urban setting in Malaysia. Subjects: TBI patients of more than six months duration with valid driving licenses, driving cars and/or riding motorcycles prior to the TBI and attended the outpatient clinic follow-up from December 2019 to June 2020 Methods: Personal and medical data were collected via face-to-face interview using a structured questionnaire and from the electronic medical record, respectively. Results: A total of 52 patients were interviewed with the average age of 39.4 (12.7) years. The commonest cause of TBI was motor vehicle accident (MVA) (86.5%) with almost half (46.1%) of the patients returned to driving post-TBI within the range of 6 months to 17 years. Majority of the post-TBI drivers (70.8%) underwent a formal driver retraining program. This study found that both the cognitive status (p < 0.05, d= 0.1) and the functional status (p < 0.05, d = 0.1) were significantly associated with return to driving. Changes in driving behavioural pattern were reported in 70.8% of the drivers. Conclusions: The rate of return to driving among patients with TBI is low. Hence there is a need to address the underlying barriers to return to drive in a comprehensive driving rehabilitation program post-TBI. Keywords: driving, rehabilitation, traumatic brain injury, vehicle